Generation of mixed murine organoids to model cellular interactions - Ana Krotenberg Garcia; Jacco van Rheenen; Saskia Jacoba Elisabeth Suijkerbuijk (STAR Protocols, 2021)
Summary: Cell competition is a mechanism of interaction that dictates cell selection based on differences in cellular fitness. We designed a protocol to generate mixed murine organoids and enteroid monolayers used to study such complex cellular interactions in a mammalian system. This protocol is dedicated to follow the behavior of different cell populations over time, using (time-lapse) microscopy or transcriptome/proteome analysis.For complete details on the use and execution of this protocol, please refer to Krotenberg Garcia et al. (2021).